THE IMPACT OF EFFECTIVE COMMUNICATION ON EMPLOYEE PERFORMANCE: In the Branch Office Environment Syariah Bumiputera Serang - Lukman, Muhammad; Pratama, Oktioza; Apfiasari, Steela (International Journal of Social and Management Studies, 2025)
Effective Communication is one of the indicators to measure the level of employee work performance in an organization. Good performance is the goal of an organization that is desired by every private and government organization. The purpose of this study is to determine the condition of the development of effective communication and the improvement of work performance (performance) in the Bumiputera Serang Sharia Branch Office environment and to determine the extent to which effective communication influences the improvement of employee performance (Idayanti et al., 2020). The method used in this study is an associative research method with data in the form of questionnaire results distributed to respondents who are all employees in the Bumiputera Serang Sharia Branch Office environment. Statistical tests used are validity tests, reliability tests, simple linear regression analysis tests and correlations to determine the validity of the data and to determine the relationship and the magnitude of the influence between effective communication on improving employee performance. To conduct the analysis, the author used SPSS 17.0 for windows. Based on the results of the study, it shows that the condition or development of effective communication has a fairly good effect on performance based on the determination coefficient test showing results with a percentage of 33.7%. Meanwhile, the remaining 66.3% is influenced by other factors that were not examined in this study.